Estimation of Some Trace Elements in Severe Head Injured Patients - Al-Adhami, Nadhia Kh.; Al-Rawi, Walid W. H.; Ibrahem, Abdulla Kh. (Journal of the Faculty of Medicine Baghdad, 2008)
Objectives: Severe head injury is the most devastating neurosurgical condition and it is only next to cancers as the leading cause of death in developed countries. Because trace elements (TEs) are involved in most of enzymes that drives the biochemical reactions, so they are considered as a window to the biochemical environment of the body in general and in brain in specific. Aim of the Study: This study measured six TEs (Fe, Zn, Mg, Cu, Mn and Co) in 29 patients with severe head injury (GCS Score 3-9); their ages between 5-50 years. Collection and estimation performed at both Neurosurgical Hospital (NH) in Baghdad and Medical Research Center (MRC) of College of Medicine, Kadhimiyah between January 2004 and August 2004. 17 of healthy Iraqi volunteers of age- and sex- matched were used as a comparable control group in TEs measurement. Results: The analysis showed that serum Cu level has a striking significant positive correlation with GCS (P<0.01) followed by serum Mg (P<0.01), serum Fe (P<0.05) with mode of correlation is linear except for that of serum Fe has three phases of correlation. Serum Mg is the only TE showed statistical significant lower value in patient group than the control group (P<0.01). Zn is the only TE that is correlated with the mode of intake, significantly lower among patient on IVF than those on N/G (P<0.01). Serum zinc correlated in linear relation with serum Mg (P<0.05), serum Fe with serum Mg (P<0.05).